Character Communication through Cognitive and Discursive Lenses - Nodira Boymurodova (Zien Journals, 2025)
This article analyzes the dialogue between characters in a literary text based on cognitive and discursive approaches. Characteristic dialogue reveals not only the personal qualities of the characters, but also their social status, cultural worldview, and psychological experiences. While the cognitive lens examines the relationship between the character's speech and the processes of consciousness and thought, the discursive lens illuminates the role of this speech in the socio - cultural context. The results of the study demonstrate the effectiveness of an integrative approach in analyzing character dialogue and provide an opportunity for a deeper interpretation of the literary text.
Keywords: character dialogue; cognitive approach; discourse